EFFECT OF AGE AND BREED ON ANTISPERM ANTIBODIES (ASA) IN BLOOD SERUM AND SEMINAL PLASMA OF BULLS: IMMUNOREACTIVITY OF SPERM SURFACE PROTEINS WITH ASA - ZODINSANGA, v; s, RANJNA; CHEEMA; MAVI, P S (The Indian Journal of Animal Reproduction, 2023)
Occurrence of ASA in blood serum / seminal plasma of bulls with respect to age / breed and immunoreactivity of sperm surface proteins with serum of bulls were determined during the present study. There was an increase of 15.3% IPA, 12.4% lgG and 9.5% lgA in serum of tested bulls with increase in age. Higher significant level of lgG antibodies and ELISA titre was detected in the serum of bulls in the age group of> 6 years, whereas, significant level of IPA/ lgA (> 10%) and higher ELISA titre in seminal plasma was detected in higher percentage of bulls in the age group of 3-6 years. Occurrence of ASA (IPA/ lgG / lgA) in serum was higher in cross-bred bulls as compared to pure-bred bulls and reverse was the case in seminal plasma. Serum of all bulls showed a reaction with sperm extracted proteins on immunoblots and a total of 19 antigens ( 16 ., 130 kDa) were detected, but only 4-10 antigens were recognized by serum in Sperm Extracts (SE) of respective bulls. lmmunofluorescence of sperm smears with serum of bulls predominantly stained post-acrosomal region, thus indicated the presence of ASA mainly against surface proteins of this region. A similarity in molecular weights of sperm proteins involved in various aspects of fertilization and that detected for immunoseropositivity with serum of presently tested bulls was found, therefore, it can be predicted that such ASA may affect the fertility of bulls. In future, the functional effects of these antibodies on bull«s fertility can be explored.